Formulasi dan Evaluasi Sediaan Salep Ekstrak Etanol Daun Semak Bunga Putih (Chromolaena odorata) sebagai Alternatif Terapi Topikal untuk Penyembuhan Luka - Laut, Meity Marviana; Ngindang, Theodora Patrisia; Novian, Dede Rival (JURNAL KAJIAN VETERINER, 2025)
Chromolaena odorata is popular as a traditional medicine in Indonesia for wound healing. In East Nusa Tenggara Province, this plant is used for wound healing. The present study aims to formulate and evaluate the natural ointment containing C. Odorata leaves extract. A total of 3.2 Kg of fresh C. odorata leaves were ground into powder, 246 g. The leaf powder was then macerated with 70% ethanol solvent for 72 hours, followed by evaporation at 60°C, resulting in 14.61 g of concentrated extract with a yield of 5.94%. The extract was formulated into ointment preparations with concentrations of 10% and 20%, using white vaseline as a basis. Alpha-tocopherol and propyl paraben were added as antioxidants and preservatives. Evaluation of the ointment preparations included organoleptic assessment, homogeneity test, pH determination, and spreadability test. The results indicated that the semi-solid cream had a dark greenish colour with the characteristic aroma of C. odorata leaf extract. The ointment preparations were homogeneous and had a safe pH value of 6.2 and 6.3 for 10% and 20% concentrations, respectively. The natural ointment exhibited good spreadability with measurements of 5.57 cm and 5.23 cm for the 10% and 20% concentrations, respectively.